Meningkatkan Pukuan Forehand pada Permainan Tenis Meja Melalui Lawan Pasif Pada Siswa Kelas VIII SMP Negeri 2 Kota Gorontalo - Iskandar Maspeke (Gorontalo State University, 2026)
Background: forehand stroke is a fundamental technique in table tennis; however, initial observations of eighth-grade students at SMP Negeri 2 Gorontalo revealed their ability toperform this technique was still low. Of the 30 students participating in the learning process, only 13 students (43%) demonstrated adequate proficiency, while 17 students (57%) were still unable to perform the technique correctly. Objective: This study aimed to improve students’ learning outcomes in performing forehand strokes through the use of wall media in Physical Education, Sports, and Health (PJOK) learning. Method: This research employed a Classroom Action Research (CAR) method conducted in two cycles involving 30 eighth-grade students (15 male and 15 female). The procedures included planning, action implementation, observation, evaluation, and reflection in each cycle. Results: The findings showed a significant improvement in student learning outcomes. In cycle I, 19 students (70%) achieved learning mastery, while 11 students (30%) had not yet achieved mastery. In cycle II, the improvement became more significant, with 27 students (90%) achieving mastery and only 3 students (10%) remaining incomplete. Conclusion: These results indicate that the use of wall media in table tennis learning effectively improves students’ forehand stroke skills and helps achieve the classical mastery criterion 80%.